The Resilience of 'Silent' Students: Re-evaluating Introversion as a Strategic Competence in EFL Learning - Ulyati Retno Sari; Sandi Pradana (LinguaScopes: International Journal of Language Education, 2026)
EFL classrooms have long treated verbal participation as the primary evidence of language learning, a conflation that places introverted students at a structural disadvantage before any instruction begins. This study examines what those students are actually doing during the silences teachers routinely read as disengagement. Twelve introverted tertiary EFL students in South Sumatra, Indonesia, participated in in-depth phenomenological interviews and Stimulated Recall Interviews (SRI) conducted against video footage of their own EFL classes. Inductive thematic analysis of the resulting data identified three superordinate themes: internal language processing, metacognitive monitoring, and learner resilience. Students were engaging in silent rehearsal, mental grammar mapping, self-monitoring, and hypothesis testing, cognitive work that left no audible trace in the classroom. Their resilience took the form of compensatory strategies and self-directed learning routines that were deliberately constructed outside class hours. These findings reposition silence as a metacognitive choice rather than an affective deficit, and introversion as a form of strategic competence that standard oral assessment rubrics cannot detect. EFL teachers need assessment and participation structures that register the range of ways learners actually engage with a language.